Serdam Sebagai Alat Musik Tiup Bambu Lampung Barat: Kajian Organologi - Uswatul Hakim; Ayuthia Mayang Sari; Hengki Armez Hidayat (FBS Universitas Negeri Padang, 2022)
Serdam is an artistic product in the form of a wind instrument, the only one in West Lampung and made of bamboo. Serdam is usually used to accompany oral literary vocals such as muayak, hahadoh, hahiwang and dance music along with other traditional Lampung musical instruments. The bamboo used for the manufacture of Serdam is bamboo of the type of bamban and is often found in the plantations of the people of West Lampung. The purpose of this study is to describe the physical form, tools and materials, the process of making Serdam, sound source and tone system and how to play the Serdam. Serdam has many physical similarities to bamboo wind instruments from other regions, but Serdam has a distinctive blowing technique and tone. The research method used is the descriptive qualitative research method. The data obtained from this study with data collection methods by observation, interviews and documentation studies. The results of this study indicate that the Serdam wind instrument is made of bamboo bamban which is often found in the plantations of the people of West Lampung. Serdam has a shape like a long tube that has four melody holes and one blow hole. This musical instrument still uses a traditional manufacturing process to this day. Serdam as the only wind instrument originating from West Lampung has many organological peculiarities that are not yet known by the supporting community.